Perancangan Logo Untuk Meningkatkan Brand Awareness AT.Net - Benny Muhdaliha; Rafli Muhamad Yuniar (Kartala Virtual Studies, 2026)
AT.Net is a local internet service provider established in 2024 under the ownership of PT Karya Media Benteng Mandiri, headquartered in Neglasari District, Tangerang City. As the company transitions from an RT/RW Net system to a professional Internet Service Provider (ISP), AT.Net faces the challenge of building a strong and consistent visual identity. Currently, AT.Net lacks an official logo that effectively represents its brand character and values. Therefore, this project focuses on logo design using a brand analysis approach and the development of a brand personality, which is then visually translated into a logo. The objective of this design is to create a visual identity that strengthens brand awareness, fosters a positive public perception, and enhances AT.Net’s competitiveness within the internet service industry. The result of this project is expected to serve as a strategic foundation for establishing a professional and trustworthy brand image for AT.Net.